The Effect of Workload, Level of Audit Fees and Audit Risk on Audit Quality: An Empirical Study of a Public Accounting Office in East Java-Indonesia - Lely Kumalawati; Made Sudarma; Aulia Fuad Rahman; Syaiful Iqbal (Australasian Accounting, Business and Finance Journal, 2024)
This study explores the variables of workload, level of audit fees and audit risk on audit quality by testing the three research hypotheses using SPSS with multiple linear regression methods. The study was conducted at a Public Accounting Firm in East Java, Indonesia, with a population of 48 officially registered auditors. A questionnaire instrument was used to collect research data, containing questions/statements related to research variables tested for validity and reliability. The collected data were analyzed using multiple linear regression methods. The research results show that workload variables, audit fees, and risk levels significantly positively affect audit quality. The main research contribution of this study is aimed at practitioners and authorities or associations that, in the preparation and implementation of audit standards, must consider the auditor's internal and external factors and the client's real condition. The association needs to bridge the mistakes of the auditor or KAP when dealing with different client conditions. In addition, based on the results of this study, it is necessary to consider work overload and working time for auditors because they affect audit quality.
Keywords: workload; level of audit fees; audit risk; audit quality